The uniqueness and iterative properties of solutions for a general Hadamard-type singular fractional turbulent flow model - Zhang, Xinguang; Xu, Pengtao; Wu, Yonghong; Wiwatanapataphee, Benchawan (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, we consider the iterative properties of positive solutions for a general Hadamard-type singular fractional turbulent flow model involving a nonlinear operator. By developing a double monotone iterative technique we firstly establish the uniqueness of positive solutions for the corresponding model. Then we carry out the iterative analysis for the unique solution including the iterative schemes converging to the unique solution, error estimates, convergence rate and entire asymptotic behavior. In addition, we also give an example to illuminate our results.
Keywords: unique solutions; turbulent flow; nonlinear operator; iterative analysis